Jirivanaea, a new name for Vitalia P.E.A.S.Camara, Carv.-Silva & W.R.Buck, hom. illeg. (Sematophyllaceae, Bryophyta) versus Vitalia Batista & Ciferri (Chaetothyriales, Ascomycota) - Deshmukh, Umakant Bhoopati; Rathor, Omprakash Shyamlal (Phytotaxa, 2021)
The genus Vitalia P.E.A.S.Camara, Carv.-Silva & W.R. Buck in Carvalho-Silva et al. (2017:825) was established by Carvalho-Silva, Camara and Buck on molecular and morphological basis, including four species, the new species “Vitalia caespitosa (Hedwig, 1801:49) P.E.A.S.Camara, Carv.-Silva & W.R.Buck in Carvalho-Silva et al. (2017:825)” as type, and three new combinations as V. cuspidifera (Mitten, 1869:480) P.E.A.S.Camara, Carv.-Silva & W.R.Buck (2017:825), V. esmeraldica (Müller Hal.,1851:392) P.E.A.S.Camara, Carv.-Silva & W.R.Buck (2017:825) and V. galipensis (Müller Hal., 1848:780) P.E.A.S.Camara, Carv.-Silva & W.R.Buck (2017:825) (Carvalho-Silva et al. 2017).However, the generic name Vitalia Batista & Ciferri (1962:105) had previously been used in botanical nomenclature of fungal Ascomycetes.